2018
DOI: 10.3386/w25116
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Wage, EITC, and Criminal Recidivism

Abstract: For recently released prisoners, the minimum wage and the availability of state Earned Income Tax Credits (EITCs) can influence both their ability to find employment and their potential legal wages relative to illegal sources of income, in turn affecting the probability they return to prison. Using administrative prison release records from nearly six million offenders released between 2000 and 2014, we use a difference-indifferences strategy to identify the effect of over two hundred state and federal minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
0
28
1
Order By: Relevance
“…Using estimates of the crime elasticity with respect to wages from Gould et al (2002), the CEA concluded that raising the Federal minimum wage from $7.25 to $12 per hour would decrease crime by 3 to 5 percent, or 250,000 to 510,000 crimes annually (CEA 2016), resulting in $8 to $17 billion dollars per year in cost savings (CEA 2016). Consistent with the CEA's prediction, recent work by Agan and Makowsky (2018) finds that minimum wage increases are negatively related to criminal recidivism.…”
Section: Introductionmentioning
confidence: 63%
“…Using estimates of the crime elasticity with respect to wages from Gould et al (2002), the CEA concluded that raising the Federal minimum wage from $7.25 to $12 per hour would decrease crime by 3 to 5 percent, or 250,000 to 510,000 crimes annually (CEA 2016), resulting in $8 to $17 billion dollars per year in cost savings (CEA 2016). Consistent with the CEA's prediction, recent work by Agan and Makowsky (2018) finds that minimum wage increases are negatively related to criminal recidivism.…”
Section: Introductionmentioning
confidence: 63%
“…Similarly,Agan and Makowsky (2018) find that being released when the EITC is more generous or when the minimum wage is higher -up to $9.50/hour -reduces recidivism.…”
mentioning
confidence: 85%
“…Even though models of criminal activity are based on individual behavior, we often test these models using aggregate area-based relationships like unemployment shocks (Agan and Makowsky, 2018;Bennett and Ouazad, 2018;Cornwell and Trumbull, 1994;Entorf, 2000;Foley, 2011;Fougere et al, 2009;Gould et al, 2002;Karin, 2005;Lin, 2008;Machin and Meghir, 2004;Raphael and Winter-Ember, 2001). Area-based relationships are meaningful and policy relevant as they inform how to broadly target crime deterrence strategies.…”
Section: Introductionmentioning
confidence: 99%